Mapping Sanitation Risk at the Hamlet Level: A Comprehensive Assessment of Sub-District in Central Jakarta - Firdaus Ali; Dwi Lintang Lestari; Marsya Dyasthi Putri; Khalidah Nurul Azmi (International Journal of Technology)
Sanitation in residential areas is significantly essential, requiring more attention, particularly in areas with dense population and developing countries such as Indonesia. High population density increases the challenges of treating solid and liquid waste produced by residents. Therefore, this study aimed to assess sanitation risk in sub-district of Central Jakarta, Indonesia, based on four indicators, namely hazard, exposure, vulnerability, and capacity. The analysis started with hazard indicators, followed by an assessment of potential exposure to hazard, and determination of vulnerability level. In the final stage, the capacity was evaluated to determine the ability of the current system to address sanitation issues. The results showed that most areas of sub-district were at low risk due to the sufficient capacity of the current system to meet the needs of residents. However, there were also areas with poor sanitation, particularly in facing natural disasters such as floods and droughts. Sanitation risk assessment used in this study provided valuable information to identify priority areas for sanitation development. The results would support the government in determining development budget priorities for sanitation infrastructure development.